Hubungan Pola Asuh Orang Tua dengan Kemandirian Anak Pra Sekolah: The Relationship between Parenting Style and Independence Preschool Children - Nurul Masitoh; Fiki Wijayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
Pre-school aged children are children with an age range of 3-6 years, where at that age the child's independence is still in a period of development. The development of independence is generally related to the child's ability to do something alone. Parenting style is one of the factors that influence children's independence. Parents' parenting style will shape the child's character which will later become a milestone in the child's life. The purpose of this study was to determine the relationship between parenting style and independence of pre-school children. This type of research is descriptive correlative with a cross sectional approach. Sampling using simple random sampling technique with a total sample of 90 respondents. The instrument used in this research is a questionnaire. The statistical test used is the chi square test. With p value = 0.003. The results of the research on parenting patterns of independent pre-school children aged 5-6 years in Pertiwi Kindergarten and Putra Bhakti Kindergarten show that most of the children's independence levels are in the moderate category of independence (56.1%) with democratic parenting (37.8%) ) authoritarian (31.1%) and permissive (31.1%). The results of the chi squere analysis obtained a p value of 0.003 <α 0.05, meaning that there is a relationship between parenting style and the independence of pre-school children aged 5-6 years. From the results of this study it can be concluded that there is a significant relationship between parenting styles and the independence of pre-school children aged 5-6 years. ABSTRAK Anak usia pra sekolah mempunyai rentang usia 3-6 tahun, dimana pada usia anak tersebut kemandirian anak masih dalam masa perkembangan. Perkembangan kemandirian umumnya berkaitan dengan kemampuan anak dalam melakukan sesuatu sendirian. Pola asuh orang tua merupakan salah satu faktor yang mempengaruhi kemandirian anak. Pola asuh orang tua akan membentuk karakter anak yang nantinya akan menjadi tonggak kehidupan anak. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan pola asuh orang tua dengan kemandirian anak pra sekolah. Jenis penelitian ini adalah deskriptif korelatif dengan pendekatan cross sectional. Pengambilan sampel menggunakan teknik simple random sampling dengan jumlah sampel sebanyak 90 responden. Instrumen yang digunakan dalam penelitian ini yaitu kuesioner. Uji statistik yang digunakan adalah uji chi square . Dengan p value= 0,003. Hasil penelitian hubungan pola asuh orang tua dengan kemandirian anak pra sekolah di TK Pertiwi dan TK Putra Bhakti diketahui bahwa sebagian besar tingkat kemandirian anak merupakan kategori kemandirian sedang (56,1%) dengan pola asuh demoktaris (37,8%) otoriter (31,1%) dan permisif (31,1%). Hasil analisa chi squere didapatkan p value 0,003 < α 0,05 artinya ada hubungan antara pola asuh orang tua dengan kemandirian anak pra sekolah usia 5-6 tahun. Dari hasil penelitian tersebut dapat disimpulkan bahwa ada hubungan yang signifikan antara pola asuh orang tua dengan kemandirian anak pra sekolah usia 5-6 tahun.